EMOTIONAL INTELLIGENCE AND MOTIVATION EFFECT ON THE PERFORMANCE OF EMPLOYEES OFFICE DISTRICT DEPARTMENT OF PLANTATION EAST KUTAI. - Jarkasi, Riyanti (PREDIKSI, 2016)
Along with the progress of the organization, the human role is very important. The success of a company or organization to achieve the goals set out of the role of human resources in it. Era of globalization all companies and organizations both profit oriented and non - profit oriented demanded to adapt, learn effectively, and capable of determining global competitiveness, based on openness to the flow of information and technology is more advanced. Human resources are the spearhead for a company or organization as well as having an important role in carrying out management functions, namely, planning, organizing, directing and supervision, the role of HR is very important in achieving organizational goals .. The main purpose of a company is to achieve maximum profit, the success of a company or organization is measured by the extent to which the company is able to achieve the goals set. The organization's goals can be achieved optimally when their management of human resources and sustainable. Human resources as the driving factor activity of the organization where the role of HR is very influential in the company's activities so that the presence of HR needs special attention from the company or organization. Human resources owned by an organization have different characteristics between individuals from one another, as well as emotional intelligence (emotional intelligence) is different. Office of Plantation East Kutai in terms of providing jobs to employees tend to be unstable in every day, because of an existing task by task within one year, when no activities related to the Plantation Office of East Kutai Regency, the employees work more relaxed. Conversely, if there is an activity or towards the end of the year, the employees will work harder and stressful than before so some employees who are less intelligent or an employee with a level of emotional intelligence is low can not understand emotions, which causes an employee to work under pressure a solid job to vent his frustration with family and work environments around. Understanding of emotions that are less precise results in a sense of emotional understanding among employees tends to be reduced. Sense of caring about the environment will be difficult to realize because of the sensitivity of the employees themselves are not properly managed.